APLIKASI METODA LINE OF BALANCE (LOB) DAN METODA CRITICAL PATH METHOD (CPM) DALAM PENJADWALAN KEGIATAN PEMBANGUNAN PERUMAHAN - Sutanto, Sutanto (Gema Teknologi, 2014)
Sutanto, in this paper explain that line of Balance is a variation of the linear scheduling method that allows the operating balance so that all activities can continue. In the various International leteratur usually shown as Line of Balance scheduling tool that is only suitable for the project - a project that is composed of repetitive activities, and is not suitable for non-repetitive projects. Network method is introduced towards the end of the 1950s by a team of engineers and mathematicians from Dupont company is working with the Rand Corporation, in an effort to develop a management control system. These systems are intended to plan and control a large number of which have a complex dependency relationship in the construction of engineering design problems and maintenance. Businesses - emphasized efforts to seek methods to minimize the costs, in conjunction with the completion of a period of activity. The system was then known as the critical path method (Critical Path Method/CPM). Research application method Line of Balance (LOB) and Critical Path Method (CPM) scheduling activities in residential construction and the impact on the field of technical constraints is one solution . Conclusions obtained from the results of the research, the use of residential construction projects activities scheduling with Line of Balance method combined with the Critical Path Method method would have added value. Keywords: Housing Development, Application lob and CPM scheduling method.